SYNERGIC EFFECT OF PREPARATION WITH COORDINATION COMPLEX “TRIMETHYDRAZINIUM PROPIONATE+ETHYMTH METHYLHYDROXYPIRIDINE SUCCINATE” ON ENERGY METABOLISM AND CELL RESPIRATION - M. V. Zhuravleva; M. V. Granovskaya; K. Ya. Zaslavskaya; Yu. G. Kazaishvili; V. S. Scherbakova; A. A. Andreev-Andrievskiy; D. I. Pozdnyakov; M. Yu. Vyssokikh (Фармация и фармакология (Пятигорск), 2022)
The article presents the results of an in vitro study of the synergetic effect evaluation of the combined preparation based on coordination complex ethylmethylhydroxypyridine succinate and trimethylhydrazinium propionate on energy metabolism and cell respiration.The aim of the study was to evaluate the mitochondria-directed action of the metabolic and antioxidant preparation based on succinic acid coordination complex with trimethylhydrazinium in relation to optimizing the energy metabolism in the cells under the oxidative stress conditions, as well as against the background of ischemic processes.Materials and methods. The study of the hydroxysuccinate complex effect of the drug Brainmax® components was carried out on isolated mouse liver mitochondria. In the course of the study, the potential of mitochondria, the generation rate of hydrogen peroxide during the respiration, the respiration rate were evaluated in the following positions: a) unstimulated by malate and pyruvate, b) stimulated by malate and pyruvate (complex I substrates), by succinate (complex II substrates), c) against the background of the initial section of the electron transport chain blockade by rotenone, d) in phosphorylation blockade by oligomycin, e) against the background of the FCCP-induced uncoupling, and f) in cyanide-blocked complex IV (cytochrome C oxidase).Results. It has been shown that the succinic acid coordination complex with trimethylhydrazinium, which is the active principle of the Brainmax® drug, significantly reduced the transmembrane potential of mitochondria (IC50=197±5 µM), compared with the widely used preparations of ethylmethylhydroxypyridine succinate and trimethylhydrazinium propionate, which facilitates the transfer of the produced ATP into the cell and preserves a vital activity of mitochondria even under stress. In the study of the mitochondrial respiration stimulated by the substrates of complex I (NADP-coenzyme Q-oxidoreductase), pyruvate and malate, the studied drug led to a more pronounced increase in the oxygen consumption with IC50=75±6 µМ. When evaluating the effect of the complex on the production of ATP by mitochondria, the most pronounced effect was observed with the addition of studied complex, which indicated to the uncoupling of respiration and oxidative phosphorylation at the given concentrations of the studied compounds. When assessing the effect of the complex on the production of hydrogen peroxide by isolated mitochondria, a significant decrease in the peroxide production was shown in the samples containing the complex of trimethylhydrazinium propionate and EMHPS.Conclusion. Based on totality of the results obtained, it can be assumed that a favorable conformation of the pharmacophore groups of ethylmethylhydroxypyridine succinate and trimethylhydrozinium propionate coordination complex included in the composition of Brainmax® leads to a synergetic interaction and more pronounced pharmacological effects on target cells. This complex provides stabilization of a mitochondrial function, intensification of the adenosine triphosphate energy production and the optimization of energy processes in the cell, reduces the severity of the oxidative stress and eliminates undesirable effects of an ischemic-hypoxic tissue damage.